Chromosomes in the flow to simplify genome analysis - Doležel, Jaroslav; Vrána, Jan; Safář, Jan; Bartoš, Jan; Kubaláková, Marie; Simková, Hana (Functional & integrative genomics, 2012)
Nuclear genomes of human, animals, and plants are organized into subunits called chromosomes. When isolated into aqueous suspension, mitotic chromosomes can be classified using flow cytometry according to light scatter and fluorescence parameters. Chromosomes of interest can be purified by flow sorting if they can be resolved from other chromosomes in a karyotype. The analysis and sorting are carried out at rates of 10(2)-10(4) chromosomes per second, and for complex genomes such as wheat the flow sorting technology has been ground-breaking in reducing genome complexity for genome sequencing. The high sample rate provides an attractive approach for karyotype analysis (flow karyotyping) and the purification of chromosomes in large numbers. In characterizing the chromosome complement of an organism, the high number that can be studied using flow cytometry allows for a statistically accurate analysis. Chromosome sorting plays a particularly important role in the analysis of nuclear genome structure and the analysis of particular and aberrant chromosomes. Other attractive but not well-explored features include the analysis of chromosomal proteins, chromosome ultrastructure, and high-resolution mapping using FISH. Recent results demonstrate that chromosome flow sorting can be coupled seamlessly with DNA array and next-generation sequencing technologies for high-throughput analyses. The main advantages are targeting the analysis to a genome region of interest and a significant reduction in sample complexity. As flow sorters can also sort single copies of chromosomes, shotgun sequencing DNA amplified from them enables the production of haplotype-resolved genome sequences. This review explains the principles of flow cytometric chromosome analysis and sorting (flow cytogenetics), discusses the major uses of this technology in genome analysis, and outlines future directions.
Keywords: Plants; karyotyp; Chromosomes; Humans; struktury chromozomu; Physical Chromosome Mapping; Oligonucleotide Array Sequence Analysis; genomika; mitóza; lidé; zvířata; malování chromozomů; Chromosome Painting; Karyotype; Flow Cytometry; genom lidský; chromozomy; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Mitosis; Chromosome Structures; průtoková cytometrie; Genome, Human; Animals; Genomics; rostliny; fyzikální mapování chromozomů; genová knihovna; Gene Library